Agricultural and Food Economics - Banterle, Alessandro; Dries, Liesbeth; Branca, Giacomo; Cembalo, Luigi
Agricultural and Food Economics (AFE) is an international peer-reviewed and open access journal published on behalf of the Italian Society of Agricultural Economics. AFE welcomes research articles from economists, scholars and researchers from all over the world to publish problem-oriented and high-quality articles. AFE publishes only original articles from a wide variety of economic perspectives that address current and relevant issues related to the agricultural and food system. AFE publishes articles focused on applied analysis, the discussion of innovative results, and relevant policy and managerial implications. AFE seeks clearly written articles from experts in the field, to promote insightful understanding of the current trends in the agri-food system.  Topics of specific interest to AFE include agricultural and food market analysis, agri-food firm management and marketing, organization of the agri-food chains, consumer behavior, food quality and safety issues, economics of nutrition and food security, food and health economics, agri-food policy and trade, sustainable rural development, natural and marine resource economics and land economics.